2009
DOI: 10.1007/s00421-009-1026-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of localized muscle fatigue on postural control and patterns of recovery during upright stance: influence of fatigue location and age

Abstract: The purposes of this study were to investigate the effects of fatigue location and age on changes in postural control induced by localized muscle fatigue, as well as the patterns of recovery post-fatigue. Groups of 16 younger (18-25 years) and 16 older (55-65 years) participants performed submaximal isotonic fatiguing exercises involving the unilateral ankle plantar flexors, knee extensors, and shoulder flexors, and bilateral lumbar extensors. Postural control was assessed during quiet upright stance, from cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 60 publications
(93 reference statements)
2
73
0
Order By: Relevance
“…Although the reliability of frequency-domain measures for postural sway, particularly mean and median power frequencies, are known to be lower than time-domain measures (Lafond et al 2004;Lin et al 2009), the reliability of quantifying force fluctuation measures, in either the time or frequency domains, have remained uninvestigated. Both the intra-and intersession reliabilities of the test measures in 16 subjects in this study were found to be excellent in the time domain.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reliability of frequency-domain measures for postural sway, particularly mean and median power frequencies, are known to be lower than time-domain measures (Lafond et al 2004;Lin et al 2009), the reliability of quantifying force fluctuation measures, in either the time or frequency domains, have remained uninvestigated. Both the intra-and intersession reliabilities of the test measures in 16 subjects in this study were found to be excellent in the time domain.…”
Section: Discussionmentioning
confidence: 99%
“…The task of maintaining upright balance is a critical component in performing most daily activities. Numerous studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have investigated the effects of muscular fatigue on the regulation of bipedal quiet upright standing. Generally, a deterioration of postural control with muscular fatigue was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the investigations cited above referred to postural control following lower limb efforts or general body fatigue. In recent years, a growing number of studies have reported increased postural sway during quiet standing with muscle fatigue localized at the lower back [7][8][9][10][11][12][13][14][15]. All of these studies assessed postural stability using laboratory measures such as a force platform; however evidence using clinical measures of postural stability is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with findings from numerous studies of participants who displayed impaired static and dynamic balance in a fatigued state. Several postural-control measures were studied in these trials, such as sway velocity, horizontal and sagittal sway magnitude, 18,32 the SEBT, 20 and the TTS. 19 Consistent negative effects on static and dynamic balance abilities were reported after local muscle and whole-body fatiguing exercise.…”
Section: Fatigue Effects On Postural Controlmentioning
confidence: 99%